IMPLEMENTASI PROGRAM GERAKAN LITERASI SEKOLAH (GLS) MELALUI WISATA LITERASI DI MIN 27 ACEH BESAR - Farah Salsabila; Nazaruddin Musa; Wahyunita Hanum (LIBRIA, 2025)
Gerakan Literasi Sekolah (GLS) is a national program aimed at fostering a culture of literacy in educational settings. This study aims to describe the implementation of the Literacy Tour program in support of the School Literacy Movement at MIN 27 Aceh Besar and to analyze the supporting and inhibiting factors. The research method used was descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results indicate that the Literacy Tour program at MIN 27 Aceh Besar has been implemented in accordance with the GLS stages established by the Ministry of Education and Culture: habituation, development, and learning. This program has been proven to increase students' interest in reading, writing skills, and courage in expressing ideas through written works. Key factors contributing to the program's success include support from the principal, teachers, and librarians, library innovation, the provision of reading corners, and parental participation. Meanwhile, inhibiting factors include limited mentors, low-grade student readiness, diverse teacher backgrounds, and a busy school schedule. The Literacy Tour program is a strategic innovation that successfully supports the effective and sustainable implementation of the GLS